Design, RNA cleavage and antiviral activity of new artificial ribonucleases derived from mono-, di- and tripeptides connected by linkers of different hydrophobicity. Issue 6 (15th March 2016) - Tamkovich, Nikolay; Koroleva, Lyudmila; Kovpak, Mikhail; Goncharova, Elena; Silnikov, Vladimir; Vlassov, Valentin; Zenkova, Marina
Graphical abstract: Abstract: A novel series of metal-free artificial ribonucleases (aRNases) was designed, synthesized and assessed in terms of ribonuclease activity and ability to inactivate influenza virus WSN/A33/H1N1 in vitro. The compounds were built of two short peptide fragments, which include Lys, Ser, Arg, Glu and imidazole residues in various combinations, connected by linkers of different hydrophobicity (1, 12-diaminododecane or 4, 9-dioxa-1, 12-diaminododecane). These compounds efficiently cleaved different RNA substrates under physiological conditions at rates three to five times higher than that of artificial ribonucleases described earlier and displayed RNase A-like cleavage specificity. aRNases with the hydrophobic 1, 12-diaminododecane linker displayed ribonuclease activity 3–40 times higher than aRNases with the 4, 9-dioxa-1, 12-diaminododecane linker. The assumed mechanism of RNA cleavage was typical for natural ribonucleases, that is, general acid-base catalysis via the formation of acid/base pairs by functional groups of amino acids present in the aRNases; the pH profile of cleavage confirmed this mechanism. The most active aRNases under study exhibited high antiviral activity and entirely inactivated influenza virus A/WSN/33/(H1N1) after a short incubation period of viral suspension under physiological conditions.